PERLINDUNGAN HUKUM TERHADAP JURNALIS WARGA YANG BERBASIS TEKNOLOGI INFORMASI - Emi Puasa Handayani (UNIVERSITAS ISLAM KADIRI, 2015)
Along with the development of technology with the invention of the internet, the speed information cannot be blocked. Black list that occurredin the print era no longer applied when the era of information technology. The problem is, when it appears journalists from citizens namely the ordinary citizens who write news or facts in blogs or personal website, then it is exposed to public whether there is any protection for the journalist. These are problems that were examined in the article titled Legal Protection Against Journalists Citizen-Based Information Technology. The results of this study can be concluded that now everyone can write and submit his writings to the audience with ease. Currently in Indonesia citizen journalism grown fairly well. This is evidenced by the number of blogs that exist in Indonesia and made by the people of Indonesia. The existence of the blog has signaled that citizen journalism is a phenomenon that is in demand and will continue to grow in the community. The nature of citizen journalism that allows all internet users can enter information that he had through the Internet, can cause a state of some kind of 'abuse of power' by the accessor. The absence of clear boundaries about what should and should not be put on the internet has made sites and blogs contain information that should not be. Therefore it needs to be a rule in the special form of legislation on the protection of citizen journalists. Keywords : Legal Protection, Citizen J